Coronary heart disease racial disparities among older adults in the U.S.: Systematic review, 2000-2024 - Sanggon Nam (Archives of Gerontology and Geriatrics Plus)
Background: Coronary heart disease (CHD) remains a leading cause of morbidity and mortality among older U.S. adults, with significant racial and ethnic disparities in prevalence, treatment, and outcomes. This systematic review synthesizes evidence from 44 studies published between 2000 and 2024 to examine these disparities among adults aged ≥65, focusing on prevalence, access to care, treatment quality, outcomes, contributing factors, and effective interventions. Methods: The review adhered to PRISMA 2020 guidelines. A comprehensive search was conducted across six databases: PubMed, Embase, Scopus, Web of Science, CINAHL, and the Cochrane Library. Studies were included if they examined racial/ethnic differences in CHD among U.S. adults aged ≥65. Two independent reviewers screened titles and abstracts, followed by full-text review, with disagreements resolved by a third reviewer. Inter-rater reliability was assessed using Cohen’s kappa (0.85 for title/abstract, 0.90 for full-text). Quality assessment used the Newcastle-Ottawa Scale (NOS; high quality ≥7 points, moderate 4–6 points, low ≤3 points) for observational studies and the Cochrane Risk of Bias tool for randomized trials. Due to heterogeneity, a narrative synthesis was conducted, with subgroup analyses for key outcomes. Results: The 44 included studies revealed persistent disparities in CHD prevalence, access, treatment, and outcomes, particularly affecting Black, Hispanic, and American Indian/Alaska Native (AI/AN) older adults. Minority groups exhibited higher CHD prevalence and risk factors (e.g., hypertension, diabetes), lower access to guideline-directed therapies, and worse outcomes, including higher readmission and mortality rates. Structural racism, socioeconomic factors, and systemic biases were key drivers. Interventions like policy reforms, community-based programs, and telehealth showed promise in reducing disparities. Conclusions: Despite progress in acute care, significant disparities persist in long-term CHD management among minority older adults. Addressing social determinants, improving access to equitable care, and implementing culturally competent interventions are essential for health equity.